Analysis of the role of PMCT during the COVID-19 pandemic: A systematic review. (September 2022) - Filograna, Laura; Manenti, Guglielmo; Grassi, Simone; Zedda, Massimo; Mecchia, Daniele; Briganti, Flavia; Ryan, Colleen P.; Pascali, Vincenzo L.; Floris, Roberto; Oliva, Antonio
Highlights: PMCT has been proposed as a forensic investigation method during the SARS-CoV-2 pandemic. Twenty publications concerned PMCT during the SARS-CoV-2 pandemic until March 2022. The most frequent PMCT lung pattern in COVID-19 was diffuse mixed densities. A very good correspondence was found between PMCT findings and histopathological results. PMCT has been proposed as a pre-autopsy screening tool or as a method for augmenting post-mortem data. Abstract: Objectives: During COVID-19 pandemic PMCT has been proposed as a forensic investigation method. This systematic review is aimed to systematize evidence and peer-reviewed opinions reported during the first two years of pandemic, to evaluate the role of PMCT during the COVID-19 pandemic. Materials and methods: An online literature search was performed to identify publications on PMCT during the COVID-19 pandemic between December 2019 and March 2022. For each publication included, the following data were collected: title and abstract, year of publication, type of article, number and type of individuals examined. The selected publications were also categorized based on PMCT findings, histopathological results, the comparison between PMCT and histopathological findings, cause of death and proposed role of PMCT during the pandemic. Results: A total of 20 publications were included, mostly case reports (9/20). All cases examined included adults. The most frequent PMCT pattern in positive cases was diffuse mixed densities with prevalence of consolidations (pattern 1) (54%). In 97% of the cases where a comparison between PMCT and histological results was performed, a correspondence was found. In 82% of the cases the principal cause of death was COVID-19 pneumonia. PMCT has been proposed as a pre-autopsy screening tool in 62%, and as a method for augmenting post-mortem data in 50% of the papers reporting this issue. Conclusion: This systematic review suggests that PMCT should be regarded as a highly valuable investigative technique for the forensic evaluation of deaths with ascertained or suspected COVID-19 pneumonia.